2019
DOI: 10.3389/fphar.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenoceptors and GRK2 as Potential Biomarkers in Patients With Chronic Pulmonary Regurgitation

Abstract: Pulmonary regurgitation (PR) is a frequent complication after repair of congenital heart disease. Three different GRK isoforms (GRK2, GRK5, and GRK3) and two β-adrenoceptors (β1-AR and β2-AR) are present in peripheral blood mononuclear cells (PBMC) and their expression changes as a consequence of the hemodynamic and neurohumoral alterations that occur in some cardiovascular diseases. Therefore, they could be useful as biomarkers in PR. A prospective study was conducted to describe the expression (TaqMan Gene E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Under physiological conditions, this process occurs during embryonic development (48), pregnancy, and through the ovarian cycle, but angiogenesis can also be reactivated in a variety of pathological conditions, including cancer (49-51), RA (52)(53)(54), ischemia (55,56) and wound healing (57). The expression and function of GRK2 is tightly modulated, and its level and functionality are altered in several pathological situations (58)(59)(60). These changes contribute to EC activation and further angiogenesis in some pathologies, which has been preliminarily proven (Table 1).…”
Section: Grk2 Mediates the Regulation Of Angiogenesis In Pathological Conditionsmentioning
confidence: 99%
“…Under physiological conditions, this process occurs during embryonic development (48), pregnancy, and through the ovarian cycle, but angiogenesis can also be reactivated in a variety of pathological conditions, including cancer (49-51), RA (52)(53)(54), ischemia (55,56) and wound healing (57). The expression and function of GRK2 is tightly modulated, and its level and functionality are altered in several pathological situations (58)(59)(60). These changes contribute to EC activation and further angiogenesis in some pathologies, which has been preliminarily proven (Table 1).…”
Section: Grk2 Mediates the Regulation Of Angiogenesis In Pathological Conditionsmentioning
confidence: 99%
“…[9,10] In two recent studies, Sikka et al [11] and Barreto Ortiz et al [12] reported that GRK2 inhibition enhanced the photorelaxation of the pulmonary artery induced by repeated blue light exposure. Additionally, both Piao et al [13] and Rodriguez-Serrano et al [14] showed that inhibiting Gβγ–GRK2 interactions improved sensitization of the failing myocardium induced by PAH. Although GRK2 is clearly implicated in a number of processes critical to the vasculature, its role in pulmonary arterial vascular smooth muscle cells (PASMCs) and PAH has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%